Clinical perspectives and treatment preferences for sertaconazole in the management of cutaneous fungal infections - S., Manjula; M., Krishna Kumar (International Journal of Research in Dermatology, 2025)
Background: Despite several clinical studies regarding the effectiveness of sertaconazole in various cutaneous fungal infections, there is a dearth of studies among clinicians. So, this study aims to assess clinician preferences and perceived efficacy of sertaconazole in the management of fungal infections across multiple dermatological indications. Methods: This cross-sectional study enrolled 599 dermatologists, and data were collected using a structured 23-item questionnaire regarding clinical characteristics, diagnostic approaches, treatment preferences, and perceived efficacy for topical antifungals, with a specific focus on sertaconazole usage. Descriptive statistics were employed for data analysis. Results: Out of 599 dermatologists, the majority (52.85%) preferred sertaconazole as the topical azole of choice for tinea pedis, while nearly 61% preferred it for tinea corporis. Clinical efficacy was rated as “very good” by approximately 42% of respondents, and 51% attributed sertaconazole’s superiority to its dual fungistatic and fungicidal activity. Occasional use was reported in pityriasis versicolor (72.56%) and seborrheic dermatitis (68.09%). About 62% of clinicians cited good efficacy as the key advantage, while 39% highlighted a combination of efficacy, tolerability, and sustained effect. The cream formulation was preferred by about 87% of participants. Conclusions: Sertaconazole is strongly preferred by clinicians for managing fungal infections in dermatology, particularly tinea pedis and tinea corporis, owing to its dual fungistatic and fungicidal activity, high perceived efficacy, and tolerability. Its expanding use in pityriasis versicolor and seborrheic dermatitis indicates growing recognition of its broader therapeutic potential.